i. (5a + 6b)^{2}

Here, A = 5a and B = 6b

(5a + 6b)^{2} = (5a)^{2} + 2 × 5a × 6b + (6b)^{2} …. [(A + B)^{2} = A^{2} + 2AB + B^{2} ]

∴ (5a + 6b)^{2} = 25a^{2} + 60ab + 36b^{2}

ii. (a/2 + b/2)^{2}

Here A = a/2 and B = b/3

(a/2 + b/3)^{2} = (a/2)^{2} + 2 x a/2 x b/3 + (b/3)^{2 }...[(A + B) = A^{2} + 2AB + B^{2}]

∴ (a/2 + b/3)^{2} = a^{2}/4 + ab/3 + b^{2}/9

iii. (2p – 3q)^{2}

Here, a = 2p and b = 3q

(2p – 3q)^{2} = (2p)^{2} – 2 × (2p) × (3q) + (3q)^{2} …. [(a – b)^{2} = a^{2} – 2ab + b^{2} ]

∴ (2p – 3q)^{2} = 4p^{2} – 12pq + 9q^{2}

iv. (x - 2/x)^{2}

Here a = x and b = 2/x

(x - 2/x)^{2} = x^{2} - 2 x (x) x 2/x + (2/x)^{2 }...[(a - b)^{2} = a^{2 }- 2ab + b^{2}]

(x - 2/x)^{2} = x^{2} - 4 + 4/x^{2}